Effect of pre-race core exercise on 50 m front crawl performance -case study focusing on individual trunk muscular activity- - Sengoku, Y.; Hasegawa, M.; Homoto, K.; Daiki, K.; Namio, D.; Miina; Muranaka; Yamakawa, K. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Activating the muscle is one of the main objectives for the warmup before competition (Bishop, 2003). In competitive swimming, swimmers need to complete their warmup inside the pool, approximately 45 min before the race for inevitable reasons (Zochowski et al., 2007). However, it is reported that the effect of the warmup lasts only for 30 min (De Bruyn- Prevest et al., 1980), there is a possibility that the effect of warmup may be diminished before the race at a competitive swimming situation. Therefore, additional pre-race strategies are needed to maintain or improve the warm-up effects. One of the procedures that can be used as a pre-race strategy is a phenomenon called postactivation potentiation (PAP). PAP is a short bout of high-intensity exercise which enables athletes to improve the muscle`s capability of generating high force over a short period of time after a proper recovery period (Sale, 2002). There are previous researchs reporting a positive effect of PAP on swimming performance (Hancock et al. 2015; Ng et al. 2020), however, there are also studies finding no change in performance after PAP exercise (Abbes et al. 2015; Sarramian et al. 2015). There is inconsistency in the effect of PAP in swimming, further research is warrented to identify the reason for different outcomes. Furthermore, most of the PAP exercise were selected to stimulate the upper or lower limbs muscle. Trunk muscle play an important role to maintain a horizontal position during swimming, and contribute to optimum production, transfer, and control of force. There are several studies reporting the effectiveness of core training on sprint performance (Weston et al, 2015; Gencer, 2018), and Matsuura et al. (2019) reported that higher intensity trunk stabilisation improves both alignment and swimming speed. However, it is not well studied whether PAP exercise targeting the trunk muscle can enhance sprint performance or not. This case study aimed to examine the effect of pre-race core exercise on 50 m front crawl performance by investigating the individual activation pattern of trunk muscles during front crawl sprint and dryland exercises in two well-trained swimmers.